An overture to overeating: The cross-modal effects of acoustic pitch on food preferences and serving behavior. (1st April 2018) - Lowe, Michael; Ringler, Christine; Haws, Kelly
Abstract: Billions of dollars are spent annually with the aim of enticing consumers to purchase food. Yet despite the prevalence of such advertising, little is known about how the actual sensation of this advertising media affects consumer behavior, including consequential choices regarding food. This paper explores the effect of acoustic pitch in food advertising, demonstrating in two studies, including a field study in a live retail environment, how the perception of pitch in advertising can impact food desirability and decisions regarding serving size. In study 1, a field study, pitch affects actual serving sizes and purchase behavior in a live, self-serve retail setting, with low pitch leading to larger serving sizes. Study 2 demonstrates how low pitch increases desire for a food product among hungry consumers, and that this effect is mediated by perceptions of size and how filling consumers believe the product will be. We discuss these results in the context of cross-modal correspondence and mental imagery.